2016
DOI: 10.15561/18189172.2016.0602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of senior pupils’ physical fitness considering physical condition indicators

Abstract: Abstract. Consideration of physical condition indicators in assessment pupils' physical fitness permits to differentiate training and health restoration processes at physical culture lessons. Purpose: to substantiate criteria for pupils' physical fitness assessment, considering their physical condition indicators. Material: in the research 10-11 form pupils (n=406; 211boys and 195 girls) participated. After physical fitness testing by requirement of acting programs we carried out diagnostic of pupils' psycho-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 2 publications
2
12
0
3
Order By: Relevance
“…It is a proof of other researches' results about reduction of these indicators [1, 2]. Our research also proves the data of authors [15,19], about Quetelet index's correspondence to normosthenic body composition. Besides, there are cases of body mass deficit or excessive body mass.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is a proof of other researches' results about reduction of these indicators [1, 2]. Our research also proves the data of authors [15,19], about Quetelet index's correspondence to normosthenic body composition. Besides, there are cases of body mass deficit or excessive body mass.…”
Section: Discussionsupporting
confidence: 91%
“…It is elucidated in many scientific works. In assessment of senior pupils' physical fitness level it was found that pupils' physical condition is out of norm: 35.6% -by body length indicators; 65% -by body mass [19]. The author notes that with age physical condition level drops [28].…”
mentioning
confidence: 97%
“…Thus, in this research we made an attempt to realize conception of eating culture among youth. Such approach is also proved in other researches [8,26]. Conclusions 1.…”
Section: Discussionmentioning
confidence: 59%
“…In the opinion of B. Abalkhail, educational programs for youth shall contain information about correct and healthy eating, optimal body mass and dimensions, use of everyday physical activity, prophylaxis of clinical obesity [1]. In other works need in urgent use of educational preventive measures on formation of young 41 people's health culture and handsome body is noted [8,45].…”
mentioning
confidence: 99%
“…In Ukraine, physical education of children and youth is one of important links of preparation for integration in society [3,4,20,29]). It is directed at improvement their physical and psychic health, perfection of readiness for active life, creative professional functioning [10,12,22,23].…”
mentioning
confidence: 99%